Growth Promoter, Immunostimulant and Antioxidant for Rainbow Trout (Oncorhynchus mykiss): Terebinth (Pistacia terebinthus) Extract - ALİ MOHAMED ALİ, Gamaia; BİLEN, Soner; GÜNEY, Kerim (Marine Science and Technology Bulletin, 2022)
In this study, the effects of Pistacia terebinthus (PT) fruit extract supplemented diet on growth performance, haematology, digestive and antioxidant enzyme activities, and non-specific immune responses were evaluated in juvenile rainbow trout (Onchoryhnchus mykiss). The fish were fed diets containing three doses of Pistacia terebinthus extract (0.1, 0.5 and 1% of diet) and a control diet without extract for 63 days. Final weight, weight gain and specific growth rate were significantly improved in all the treated groups. In addition, feed conversion ratio was significantly reduced in all PT diet fed groups. Pepsin and lipase activities were significantly increased in all the treated groups. Trypsin was significantly improved in PT 0.1% and PT 1% groups. Amylase was significantly increased in PT 0.5 and 1% groups. In haematological assays, red blood cell, haemoglobin, haematocrit, mean cell volume, mean cell haemoglobin, mean cell haemoglobin concentration values were not changed among all experimental groups. Superoxide dismutase, catalase, glutathione peroxidase and glucose-6-phosphate dehydrogenase activities were significantly improved in all the treatment groups. However, catalase activity decreased in PT 0.5% group at the end of 63 days. In addition, hepatic and white muscle lipid peroxidation activities were significant decreased in all the treated groups compared to the control. Non-specific immune parameters, such as nitroblue tetrazolium reduction, myeloperoxidase and lysozyme activities were increased in all the treated fish groups. These results indicated that extract of P. terebinthus can be used to improve fish health in aquaculture.
Keywords: Hidrobiyoloji; Hydrobiology; Pistacia terebinthus; Onchoryhnhus mykiss; Growth promoter; Immune responses; Health management; 6. Clean water; 3. Good health